If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -8) + -1(6x + 4) = 0 Reorder the terms: (-8 + x) + -1(6x + 4) = 0 Remove parenthesis around (-8 + x) -8 + x + -1(6x + 4) = 0 Reorder the terms: -8 + x + -1(4 + 6x) = 0 -8 + x + (4 * -1 + 6x * -1) = 0 -8 + x + (-4 + -6x) = 0 Reorder the terms: -8 + -4 + x + -6x = 0 Combine like terms: -8 + -4 = -12 -12 + x + -6x = 0 Combine like terms: x + -6x = -5x -12 + -5x = 0 Solving -12 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -5x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -5x = 0 + 12 -5x = 0 + 12 Combine like terms: 0 + 12 = 12 -5x = 12 Divide each side by '-5'. x = -2.4 Simplifying x = -2.4
| -20=-5+5y | | 100x-35= | | 5+1/8x=15 | | q-25=81 | | 9x-3y=81 | | 2(6y-4)-x=-4(y-3) | | u^2-u-42=0 | | 12x-4y=96 | | 2x-4=5x-24 | | 4(x-15)=16x | | 12=3w+6 | | 2(3y-6)=5(y+2) | | 4x-7=15x+4 | | X+4/2x=4 | | x/3=10+15 | | 5x-8x+3=x-2+5 | | 0.12y+0.02(y+5000)=600 | | 3y+12=9y-18 | | 4/6x+2=6 | | 9x+2=11x-2 | | 8(x+7)+8=8x+2 | | 1/4(x-12)+1/2(x+2)=x+4 | | 6x+2x=36+12 | | 9+8a+17/3=-2 | | 2/5x+10 | | 6x+30=5(x-5)+x | | 2x-10=3x-16 | | 6x+20=4x+38 | | 11x-2(x-2)=9(x+1)+9 | | 4(n-1)=-20 | | 1/5y^4-7y+3y | | lm-6l=27 |